2016
DOI: 10.3390/v8080211
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Seroprevalence in Europe: A Meta-Analysis

Abstract: There have been large numbers of studies on anti-HEV IgG seroprevalence in Europe, however, the results of these studies have produced high variability of seroprevalence rates, making interpretation increasingly problematic. Therefore, the aim of this study was to develop a clearer understanding of anti-HEV IgG seroprevalence in Europe and identify risk groups for HEV exposure by a meta-analysis of published studies. Methods: All European HEV-seroprevalence studies from 2003 to 2015 were reviewed. Data were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
189
3
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(224 citation statements)
references
References 49 publications
21
189
3
11
Order By: Relevance
“…Previous studies suggest that at any given time at least 20% of pigs are excreting HEV in their feces, and it is likely that significant amounts of HEV enter watercourses through run-off from pig farms [15] . A number of studies, including a meta-analysis, looking at HEV seroprevalence in Europe linked contact with swine and wild animals with significantly higher seroprevalence rates than those seen in the general population [16] .…”
Section: Epidemiology Of Hepatitis E In Developed Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that at any given time at least 20% of pigs are excreting HEV in their feces, and it is likely that significant amounts of HEV enter watercourses through run-off from pig farms [15] . A number of studies, including a meta-analysis, looking at HEV seroprevalence in Europe linked contact with swine and wild animals with significantly higher seroprevalence rates than those seen in the general population [16] .…”
Section: Epidemiology Of Hepatitis E In Developed Countriesmentioning
confidence: 99%
“…In hyperendemic developing countries, somewhat predictably, rates ranging from 16 to 61.9% [21,22] have been reported. A recent meta-analysis found that seroprevalence rates in Europe vary significantly, from 7.5% in Italy to 12.7% in the UK and as high as 32% in France [16] . In the past, the seroprevalence in these countries was thought to be much lower, with early studies suggesting rates <5% [23] .…”
Section: Seroprevalencementioning
confidence: 99%
“…Again, these estimates depend on the used assay [28]. In humans, seroprevalence in the general population (blood donors) in Europe ranged from 0.6 to 52.5% [32]. Higher prevalence estimates were demonstrated for professional risk groups with direct contact to domestic pigs as well as for hunters and forestry workers [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, HEV GT 1 and 2 are obligate human pathogens and mainly transmitted via contaminated drinking water in regions with low sanitation, while zoonotic transmission, predominantly by infected swine meat, seems to be the major source of HEV GT 3 and 4 transmission [4,6,7]. In addition, it has been shown that either people in contact with animals or forestry workers have a higher risk for anti-HEV immunoglobulin G (IgG) positivity, demonstrating that these present risk factors for contact with HEV [8]. Moreover, HEV GT 1 infection is associated with fulminant hepatitis and fatal outcomes in pregnant women, but no such association has been observed in zoonotic hepatitis E.…”
Section: Introductionmentioning
confidence: 99%